Asthma Education and Management Programs in Canada - Robert L Cowie; Lisa Cicutto; Louis-Philippe Boulet; the Patient Education Program Committee, Canadian Network For Asthma Care (Canadian Respiratory Journal)
OBJECTIVE: To establish the number and type of asthma patient education programs throughout Canada.